Bacterial Whole-Genome-Resequencing Analysis: Basic Steps Using the CLC Genomics Workbench Software. - Zeden,MS; Gründling,A (Cold Spring Harb Protoc, 2023)
In this protocol, we describe the basic steps for bacterial genome resequencing analysis using the QIAGEN CLC Genomics Workbench software. More specifically, we present how a reference genome sequence can be generated from Illumina reads of a wild-type reference bacterial strain and how this reference genome sequence can then be used to identify genomic alterations in mutant strains. As specific examples, Illumina reads from the Staphylococcus aureus RN4220 strain will be used to generate a consensus reference genome based on the publicly available S. aureus NCTC8325 genome sequence. The generated RN4220 consensus reference genome will subsequently be used to identify genomic mutations in an RN4220 mutant strain with increased oxacillin resistance (OxaR strain).